THE ROLE OF TRUST AND FORGIVENESS IN MARITAL INTIMACY ON HUSBANDS OR WIVES OF DUAL-EARNER COUPLES IN SURABAYA - Avanti, Fibia Tista; Setiawan, Jenny Lukito (Jurnal Ilmu Keluarga dan Konsumen, 2022)
Intimacy is very important in determining the longevity of a marriage. In East Java, Surabaya is the fourth city with the highest number of divorces, with 4938 couples deciding to divorce in 2016 (JPNN, 2017). This study aimed to analyze the role of trust and forgiveness towards marital intimacy in dual-earner husbands or wives in Surabaya. This study used a quantitative research design. Populations in this study were working individuals with a working spouse (including part-time and freelance), living in Surabaya, and still engaged in marital relationships. The study sample consisted of 107 subjects selected using the convenience sampling technique. Data collection was obtained through an online questionnaire on Google Forms. Data analysis was carried out using multiple linear regression tests on the JASP (Jeffreys’s Amazing Statistics Program) program. The results showed that trust and forgiveness played a significant role in marital intimacy in dual-earner husbands or wives (F(2,104) = 48,46; p<0,001). Only trust had a significant effect on marital intimacy (t = 7,375; p<0,001) whereas forgiveness had no significant effect on marital intimacy (t = 1,394; p > 0,05).